حماية درنات البطاطا من التعفن الجاف بالعلاج الوقائي ومدى صلاحيتها لعمل الجبس - حسن, وزير علي; حميد, رجب ابراهيم; فقي, صالح علي (Sulaimani Journal for Pure and Applied Sciences, 2002)
C and 80 — 85 % Curing of potato tubers c. v. " Clauster " was investigated at 15,20 RH for periods 7, 14 and 21 days , after wounded and inoculated with Fusarium solani , in addition to evalution their validity for chips processing . Results indicated that the curing of tubers showed a significant reduction in the weight C for 14 — 21 days , loss and dry rot incidence , although it's susceptibility when treated at 20 No effects were detected on dry weight and total soluble solids ( Tss) . However net percent C for 21 days ,since their turbers had the of chips / tubers were increased when applied at 15 highest content of dry matter . Quality of chips influenced by Tss content, therefor . the lowest Tss percent gave the better chips .